P12 Twig-like MCA: a vascular anomaly associated with aneurysms. (29th August 2022) - Lorga, T; Tavares, J; Freire, I; Gil, I; Baptista, T
Abstract : Twig-like MCA is an extremely rare entity, believed to result from the persistence of the fetal intracranial arterial network that normally merges into a definitive MCA. This vascular lesion is frequently misdiagnosed, and seems to be related to a higher incidence of aneurysms and susceptibility to both ischemic and hemorrhagic strokes. We report a case of a 37-year-old woman who was submitted to endovascular treatment of an AComA ruptured aneurysm associated with a left twig-like MCA. This case highlights the clinical impact of twig-like MCA and emphasizes its uncertain follow-up strategy.